The Recovery Factor Analysis on Heavy Oil Under Electromagnetic Heating Treatment - Gerry Sasanti Nirmala; Diyah Rosiani; Dedi Irawan; Ismail Halim (Scientific Contributions Oil and Gas, 2025)
The use of electromagnetic heating mechanisms in heavy oil production operations is widely limited in Indonesia. In this context, there is a need for in-depth research regarding the effectiveness of the method. Therefore, this research aimed to discuss the efficacy of heating method through Recovery Factor (RF) analysis using imbibition with electromagnetic waves and the addition of nanopowder. The results showed that the speed of heating and RF imbibition using electromagnetic waves was higher than conventional imbibition. In addition, ferrous oxide nanopowder produced the highest heating speed and RF of 38.39% below the expected value. Further research could be conducted regarding changes in the wettability of rock due to electromagnetic heating and nanopowder required to answer the problem.